Study of orientation of spin vectors of near infrared galaxies of low redshifted SDSS DR-19 Galaxies - Yadav, Birendra Prasad; Yadav, Shiv Narayan; Jha, Ajay Kumar; Devkota, Ram Chandra (BIBECHANA, 2026)
This study presents an analysis of the spatial orientations of 492,268 SDSS galaxies with redshifts ranging from 0.010 to 0.150, utilizing data from the 19th data release (DR19). The primary objective of this research is to investigate the nonrandom effects associated with the orientations of angular momentum in galaxies within the specified redshift range, evaluated through three distinct scenarios: the Hierarchy model, the Pancake model, and the Primordial Vorticity model. The analysis involves transforming the two-dimensional observational data—including positions, position angles, and inclination angles—into three-dimensional rotation axes characterized by polar and azimuthal angles. This transformation is accomplished using the position angle-inclination method. Our principal aim is to explore the relationship between spatial orientation and the z-magnitude in low-redshift galaxies. Expected isotropic distribution curves are generated by accounting for selection effects and conducting a random simulation that produces 107 virtual galaxies. To compare the observed and expected distributions, we employ four statistical tests: Chi-square analysis, Autocorrelation, First order Fourier Coefficient and first order Fourier Probability. An equatorial coordinate system has been selected as our reference; however, it is noteworthy that the observed preferred alignments are consistent regardless of the coordinate system employed. Despite this, localized anisotropies are evident in several samples, suggesting the potential influence of gravitational tidal interactions among neighboring galaxies and an early merging process that may alter the initial alignment of nearby galaxies. Specifically, samples z01, z02, z03, z04, z05, z06, z07, z10, z11, and z17 exhibit isotropy and remaining samples exhibit anisotropy in the polar angle (θ) distribution, while samples z01, z02, z03, z04, and z12, to z19 exhibit isotropy and remaining samples exhibit anisotropy in the azimuthal angle (φ) distribution. Some of the identified local anisotropies may be attributed to tidal interactions between galaxies or gravitational shearing effects, as indicated by previous studies. A follow-up multi-wavelength investigation is recommended to gain further insights into these phenomena.